Seismic performance of H-section beam to HSS column connection in prefabricated structures. (November 2017) - Liu, X.C.; Yang, Z.W.; Wang, H.X.; Zhang, A.L.; Pu, S.H.; Chai, S.T.; Wu, L.
Abstract: This paper proposes a new type of bolted assembly joint for connecting an H-shaped steel beam to a square HSS column and connecting HSS columns between each other in a prefabricated high-rise steel structure. The welding of components within the same module is completed in the factory, and the modules are assembled with bolts on site. The columns are connected via flanges and bolts; the H-shaped steel beam and HSS column are connected via cover plates that extend from the flanges, end-plates of the column base, and beam end stiffeners. Rigid and variable stiffness beam-to-column connections can be obtained by adjusting the number and specification of the bolts. The stiffness of the variable stiffness connection varies with the load. Thus, the connection can be rigid in a weak earthquake, yet the cover plate and beam flange can slip over each other strong earthquakes, which dissipates energy by slipping. The hysteretic performances of 9 joints were analysed by finite element analysis (FEA) and were tested in the paper; seismic performance metrics, such as hysteretic performance, ductility, and rotation capacity, were obtained. The bolt number, gap between the bolt shank and the bolt hole, thickness of the flange and the cover plate that impact the mechanical performance of the joint were analysed, and the slipping characteristics of the contact surface were obtained. The slipping between the cover plate and beam flange increases the assembly's capacity of deformability, ductility, energy dissipation, and slipping energy dissipation without significantly reducing its ultimate bearing capacity. Graphical abstract: Highlights: A new type of bolted beam-column joint for high-rise steel structures is presented. Cover plate slips relative to beam flange to dissipate energy during an earthquake. Connection stiffness can be controlled by adjusting the number or size of the bolts. Parameter analysis on the joint's seismic properties was conducted via cycling tests. Bolted slip connection raises the joint's ductility and energy dissipation capacity.